Implementation of the Attractive Learning Model in Learning Moral Beliefs at Mts Negeri 4 Bungo - Ferita Meliana; Muhammad Solihin; Ulfa Adilla (Journal Emerging Technologies in Education, 2026)
Learning Akidah Akhlak in madrassas requires a strategy that not only emphasizes theoretical mastery of the material, but also the formation of Islamic attitudes and behaviors of students in daily life. The problems that arise in this study are related to the tendency of teacher-centered learning, the limitations of class interaction, and the lack of optimal involvement of students in understanding and living the material of Moral Faith. This study aims to analyze the implementation of the interactive learning model in learning Akidah Akhlak at MTs Negeri 4 Bungo, including the form of implementation, supporting and inhibiting factors, and its impact on students' understanding and behavior. The research uses a qualitative approach with a descriptive method. Data was collected through observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaa models through data reduction, data presentation, and conclusion drawn. The results of the study show that the interactive learning model has been applied through discussions, questions and answers, presentations, educational games, and technology-based media so that learning becomes more active, communicative, and student-centered. The supporting factors include student enthusiasm, school support, and the use of interactive media, while the inhibiting factors include limited facilities, low confidence of some students, and limited learning time. In conclusion, the interactive learning model is effective in improving the quality of learning Akidah Akhlak, strengthening students' understanding, and encouraging the formation of discipline, responsibility, cooperation, and mutual respect.